ЛАКУНЫ, СВЯЗАННЫЕ С ОТВЛЕЧЕННЫМИ ПОНЯТИЯМИ, ПРОЦЕССАМИ (Eurasian Journal of Philology Science and Education, 2015)
The article is dedicated to the lacunae connected with abstract conception, process (time, action, motion, ache, height, qualities etc). Such lacunae are analysed on the most interesting facts and examples from the Russian, Azerbaijanian and English languages. Is emphasized the different perception of reality by different peoples according to their mentality, nationalconscience and world-conception.